PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PADA PT. AIRMAS PERKASA - Hadi, Reza Khairul; Sulaeman, Asep; Komarudin, Komarudin (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The quality of products on consumer satisfaction at PT. Airmas Perkasa is good both partially and simultaneously. The method used is quantitative. The population consists of consumers who purchase IT & Electronics products, with a sample collection technique using the Slovin formula, resulting in a sample of 98 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. The results of this study show that service quality partially influences positively and significantly on consumer satisfaction with a determination coefficient value of 80.6%, as evidenced by the hypothesis test results where the t-value > t-table (19.961 > 1.985). Product quality partially influences positively and significantly on consumer satisfaction with a determination coefficient value of 83.9%, as evidenced by the hypothesis test results where the t-value > t-table (22.361 > 1.985). Service quality and product quality simultaneously have a positive and significant influence on consumer satisfaction with the regression equation Y = 4.289 + 0.263X1 + 0.494X2. The determination coefficient value is 85.9%, as evidenced by the hypothesis test results where the F-value > F-table (289.216 > 3.091). Therefore, H0 is rejected, and H3 is accepted. This means that service quality and product quality have a positive and significant simultaneous influence on consumer satisfaction.